1981
DOI: 10.1111/j.1600-0609.1981.tb01644.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Peroxidase Activity in Whole Blood of Patients with Sickle Cell Anaemia

Abstract: Whole blood glutathione peroxidase was found significantly increased relative to controls in a group of 21 black patients with sickle cell anaemia. One control group consisted of 15 normal black subjects. A second control group, consisting of 21 black patients with various abnormal haemoglobins including a‐thalassaemia, also showed a tendency to enhanced glutathione peroxidase activity, confirming previous reports that elevated glutathione peroxidase levels are secondary to a variety of haemolytic conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the largest study, Chiu et al observed a significantly lower plasma vitamin E level (0.61 mg/dl) in 54 children and young adults with sickle cell disease than did 16 normal control subjects (0.89 mg/dl). It is of interest that sickle red cells have what may be compensatory increases in the activities of glutathione peroxidase [78,79] and superoxide dismutase [80]. It is of interest that sickle red cells have what may be compensatory increases in the activities of glutathione peroxidase [78,79] and superoxide dismutase [80].…”
Section: Fat Soluble Vitaminsmentioning
confidence: 99%
“…In the largest study, Chiu et al observed a significantly lower plasma vitamin E level (0.61 mg/dl) in 54 children and young adults with sickle cell disease than did 16 normal control subjects (0.89 mg/dl). It is of interest that sickle red cells have what may be compensatory increases in the activities of glutathione peroxidase [78,79] and superoxide dismutase [80]. It is of interest that sickle red cells have what may be compensatory increases in the activities of glutathione peroxidase [78,79] and superoxide dismutase [80].…”
Section: Fat Soluble Vitaminsmentioning
confidence: 99%